How Should Liberal Democratic Governments Treat Conscientious Disobedience as a Response to State Injustice?: A Proposal. (May 2022) - Wong, Brian; Chan, Joseph
Abstract: This paper suggests that liberal democratic governments adopt a reconciliatory approach to conscientious disobedience. Central to this approach is the view – independent of whether conscientious disobedience is always morally justified – that conscientious disobedience is normatively distinct from other criminal acts with similar effects, and such distinction is worthy of acknowledgment by public apparatus and actors. The prerogative applies to both civil and uncivil instances of disobedience, as defined and explored in the paper. Governments and courts ought to take the normative distinction seriously and treat the conscientious disobedients in a more lenient way than they treat ordinary criminals. A comprehensive legislative scheme for governments to deal with prosecution, sentencing, and imprisonment of the conscientious disobedients will be proposed, with the normative and practical benefits of such an approach discussed in detail.